Study on Stability of Small Clearance Shield Tunnel Excavation Face - GAO Qi (Chengshi guidao jiaotong yanjiu)
［Objective］ Determine the limit support pressure required to maintain tunnel face stability during the construction of double-line small clearance shield tunnel. ［Method］ The excavation stability of double-line small clearance shield tunnel is studied by using a combination of numerical simulation, theoretical analysis and engineering verification. Numerical simulation is used to analyze the instability mode and limiting support pressure of double-line small clearance shield tunnel face. Based on the numerical simulation results, an analytical model for the instability of a double-line shield tunnel excavation face is proposed, and the limit support pressure required to maintain the tunnel face stability is derived by using the limit equilibrium theory. ［Result & Conclusion］ During the construction process of the small-clearance shield tunnel, a combined soil arch will be formed. Under the action of the combined soil arch, the limit support pressure required to maintain the stability of the double-line small-clearance tunnel excavation surface will increase significantly. Theoretical analysis shows that when the clearance is less than 0.5 D (D is the tunnel diameter), the limit support pressure increases with the increase of the clearance; when the clearance exceeds 0.5D, the limit support pressure decreases with the increase of the clearance; when the clearance exceeds 2.0D, the combined soil arch cannot be formed, and the failure mode in this case is the same as that of the single-hole tunnel, and the clearance no longer affects the limit support pressure.